Analysis Of Environmental Audit Implementation On Rubber Waste Management PTPN IV Regional 1 Kebun Gunung Para - Vitryani Tarigan; Wico Jontarudi Tarigan; Indra Gunawan (Jurnal Ilmiah Accusi, 2024)
This research aims to determine the implementation of an environmental audit of waste management at the PTPN 1V Regional 1 Kebun Gunung Para rubber factory. The object of this research is the Processing Factory PT. Perkebunan Nusantara 1V Regional 1, Kebun Gunung Para.The data collection techniques used in this research are interview techniques and documentation techniques, where interviews are carried out by asking several questions with direct communication between the researcher and the resource person to obtain information related to the problems in this research. Meanwhile, documentation techniques are data obtained directly from the company related to research data which includes: environmental audit SOPs, waste management SOPs and the company's annual costs regarding waste processing costs. The data analysis technique used by researchers is a qualitative descriptive analysis technique, describing the findings later and comparing them with the SOP created by the company. The results of this research reveal that PTPN 1V Regional 1 Kebun Gunung Para is good and in accordance with the SOP in carrying out an Environmental Audit of waste management at the Kebun Gunung Para Rubber Factory, This can be seen from the SOP that has been set by the company and the results of field observations and direct interviews with Gunung Para Garden employees